Experimental behaviour of bridge falsework joints - André, J. (2013)
Bridge falsework systems, in particular those constituted by proprietary modular framed systems of metallic elements connected by special couplers are frequently used in structural engineering works. The popular Cuplok® system was chosen for this study. A total of 192 tests were carried out divided in four types of joints. For each type of joint, several pa-rameters, critical to define the joints’ behaviour, were analysed statistically. The selection of the probabilistic distribution for each parameter was based on classic goodness of fit tests but also on more advanced analysis. The results show that in some cases the most suited distribu-tions deviate greatly from normality.